2012
DOI: 10.1134/s1063784212060266
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of thermoelectric conversion in ferroelectric film capacitive structures

Abstract: 792Nowadays, semiconductor photovoltaic elements, more specifically, solar cells of different types, offer the most effective conversion of optical radiation energy to electrical energy. However, all photovoltaic devices have a common disadvantage: frequency selectivity, which keeps them from converting heat fluxes in a wide frequency range. Therefore, there arises the need for new approaches to energy conver sion and new efficient materials for converters.The capacitive way of converting the thermal energy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…On the other hand, such temporal temperature variations can be an advantage for another application, the pyroelectric effect, which can also directly convert heat into electricity . To date, considerable effort has been devoted to investigating the pyroelectric effect to develop a useful renewable energy source based on theoretical investigations, materials, and systems .…”
Section: The Pzts (Fuji Ceramics Co Ltd Japan) Used In This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, such temporal temperature variations can be an advantage for another application, the pyroelectric effect, which can also directly convert heat into electricity . To date, considerable effort has been devoted to investigating the pyroelectric effect to develop a useful renewable energy source based on theoretical investigations, materials, and systems .…”
Section: The Pzts (Fuji Ceramics Co Ltd Japan) Used In This Studymentioning
confidence: 99%
“…[9][10][11][12] To date, considerable effort has been devoted to investigating the pyroelectric effect to develop a useful renewable energy source based on theoretical investigations, materials, and systems. [13][14][15][16][17][18] In the 1980s, Olsen et al reported on an electrothermodynamic cycle (Olsen cycle) using the pyroelectric effect and an external electric field, [19,20] which can be described by a loop of electric displacement, D, versus the electric field, E (D-E loop).…”
mentioning
confidence: 99%
“…Thermal energy from the Sun can also be converted directly to electricity by means of thermoelectrics [16], ferroelectrics [17], magnetohydrodynamics [18], and electrogasdynamics [19]; clear opportunities through which Physics will contribute to the envisioned technological evolutions within the decade 2017-2027. In all these technologies, the iconic innovations will lie in improving the efficiency of the technologies' associated power systems, as well as use of locally available resources, so as to guarantee cost-effectiveness and affordability.…”
Section: Introductionmentioning
confidence: 99%